Latchem, Colin (2012) Quality assurance toolkit for open and distance non‐formal educationCommonwealth of learning (Vancouver) isbn 978‐1‐894975‐50‐6 98 pp CDN$12 (or free download) http://www.col.org/resources/publications/Pages/detail.aspx?PID=403. (13th August 2013) - Smyth, Robyn
Summary: Colin Latchem's quality assurance toolkit for non‐formal education (nfe ) will serve a variety of readers well. It demonstrates clearly how technology of any generation can be used to improve outcomes for peoples who are disadvantaged, remotely located or of low status. Its presentation of a pragmatic quality assurance framework moves social justice agendas forward. If the content of this book is likely to be relevant to you, I recommend that you arrange to borrow a copy for a while. Robyn Smyth